The terrible thing that happened to Barnaby Brocket - Boyne, John, 1971-; Jeffers, Oliver (New York : Alfred A. Knopf, 2013)
Born with an ability to float in the air, Barnaby Brocket is entreated by his parents to hide his unusual trait until a fateful day when he finds himself on a journey that takes him all over the world and into outer space.
Keywords: Families -- Juvenile fiction; Runaway children -- Juvenile fiction; Adventure fiction